2018
DOI: 10.1590/s0100-83582018360100002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Performance of Seeds and Level of Herbicide Residues Depending on Application of 2.4-D in Wheat

Abstract: -Horseweed control through application of 2.4-D in the winter season is an alternative to manage biotypes resistant to herbicides that belong to other mechanisms of action. The objectives of this study were to assess the physiological quality of wheat seeds and determine the rate of 2.4-D residue, as function of application stages and herbicide rates. The treatments were arranged in factorial scheme, with three application stages (flowering, soft dough and hard dough), and four 2.4-D rates (0; 504; 1,008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Regarding the contact of 2,4-D with seeds, the literature can be conflicting. That is, some studies prove that the herbicide is capable of altering the physiological quality of seeds, such as wheat, resulting in increased speed and total percentage of germination, while accumulating in the grain, even in concentrations below the maximum permitted limit (AISENBERG et al, 2018). On the other hand, another study reported that wheat seeds pretreated with 10μM 2,4-D for 48h induced antioxidant activity and protective effect against salt stress (MOHSIN et al, 2020).…”
Section: P á G I N a | 835mentioning
confidence: 99%
“…Regarding the contact of 2,4-D with seeds, the literature can be conflicting. That is, some studies prove that the herbicide is capable of altering the physiological quality of seeds, such as wheat, resulting in increased speed and total percentage of germination, while accumulating in the grain, even in concentrations below the maximum permitted limit (AISENBERG et al, 2018). On the other hand, another study reported that wheat seeds pretreated with 10μM 2,4-D for 48h induced antioxidant activity and protective effect against salt stress (MOHSIN et al, 2020).…”
Section: P á G I N a | 835mentioning
confidence: 99%